Perancangan Komik Strip Digital Islami Sebagai Media Edukasi Dalam Pendidikan Adab Pada Remaja - Arrafie Smart Satya Nugraha; Diana Aqidatun Nisa (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This journal discusses the design of Islamic digital comic strips as educational media in adab education for teenagers. The significant development of technology has changed the way humans receive information. This research aims to design a digital comic strip that is innovative and effective in conveying Islamic manners values to teenagers. Using the research method of relevant literature studies and observations of appropriate comic strip content, the process and results of designing digital comic strips will meet the standards of the times and successfully achieve the objectives of designing comic strips as educational media in ettiquete education for adolescents. The results of this study can provide theoretical insights into the design of comic strips that are effective and in accordance with the times.